Melatonin Enhanced the Tolerance of Arabidopsis thaliana to High Light Through Improving Anti-oxidative System and Photosynthesis - Yang, Si-Jia; Huang, Bo; Zhao, Yu-Qing; Hu, Di; Chen, Tao; Ding, Chun-Bang; Chen, Yang-Er; Yuan, Shu; Yuan, Ming (Frontiers in Plant Science, 2021)
Land plants live in a crisis-filled environment and the fluctuation of sunlight intensity often causes damage to photosynthetic apparatus. Phyto-melatonin is an effective bioactive molecule that helps plants to resist various biotic and abiotic stresses. In this study, we demonstrated that melatonin enhanced the tolerance of Arabidopsis thaliana to high light. Results showed that exogenous melatonin increased photosynthetic rate and protected photosynthetic proteins under high light. This was mainly owing to the fact that exogenous melatonin effectively decreased the accumulation of reactive oxygen species and protected integrity of membrane and photosynthetic pigments, and reduced cell death. Taken together, our study promoted more comprehensive understanding in the protective effects of exogenous melatonin under high light.